Allelopathic potential of Ipomoea fistulosa on the germination of lettuce and tomato - Lima, Juliana Domingues [UNESP]; Moraes, Wilson da Silva (My University, 2008)
The objective of the present research was to determine the allelopathic potential of Ipomoea fistulosa plants on germination and growth of seedlings. In laboratory, lettuce and tomato seeds were placed to germinate in the presence of water or Ipomoea fistulosa leaf extract, in the concentrations of 5, 10 e 15% (p/v). In greenhouse, seeds were placed to germinate in trays containing Plantmax® substrate and Plantmax® substrate + Ipomoea fistulosa dry leaf residue, at 3% (w/w). The aqueous extract inhibited germination, raised the mean germination time of the seeds and reduced the radicle and hypocotyl growth in all used concentrations. In greenhouse, the plant height, leaf number, and dry mass accumulation also were reduced in the presence of the leaf residue in the substrate. The results suggest the presence of allelochemicals in Ipomoea fistulosa and demonstrate the highest sensitivity of lettuce that tomato to these compounds.
Potencial alelopático de Ipomoea fistulosa sobre a germinação de alface e tomate
Keywords: Alellopathy; Ipomoea fistulosa; Weed